PKM Pembuatan Kripik Ubi dan Keladi pada PKK di Desa Setalik Kecamatan Sejangkung Kabupaten Sambas Provinsi Kalimatan Barat - Muslimah Muslimah; Kiki Kristiandi; Hikmah Trisnawati; Irma Fahrizal Butsi Ningsih (I-Com: Indonesian Community Journal, 2025)
Setalik Village is one of the villages that has the potential to develop its agricultural products. The agricultural products of this village are cassava, taro and other abundant agricultural products. This Community Service Program (PKM) aims to improve the skills of PKK mothers in Setalik Village, Sejangkung District, Sambas Regency, in processing sweet potatoes and taro into chips with economic value. The approach taken in this service is divided into 5 stages, namely the licensing process, selection of raw materials, cooking process, economic calculations and evaluation. This activity involved 15 participants who were members of the PKK mothers and facilitated by lecturers from the Sambas State Polytechnic. In this training, participants were given material and direct practice in making sweet potato and taro chips, starting from preparing materials, processing techniques, to product packaging. The results of the activity showed that participants were able to understand and apply chip making techniques well. It is hoped that this activity can be the first step in developing sustainable home businesses and improving the economy of the local community.